1998
DOI: 10.1023/a:1008955002955
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the osteoblast response to a silica gel in vitro

Abstract: Many bioactive glasses and glass ceramics contain silica, yet the effect of silica on the osteoblast is not well understood. The osteoblast cell response to a silica surface, without the interference of the other ions present in glasses and glass ceramics has been investigated. A silica sol-gel was prepared which gave a molar ratio of 1:4:4 tetraethyl orthosilicate (TEOS): ethanol:acidified water 0.2 M HCl) and spin cast on to thermanox discs. The gel was characterized in terms of bioactivity and release of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 11 publications
3
25
0
1
Order By: Relevance
“…[14][15][16][17] Finally, the use of scaffold material and surface modifications, such as a calcium phosphate coating, can play an important role in stimulating the osteogenic potential of stromal cells. [18][19][20] In view of the aforementioned, our previous studies with titanium fiber mesh indicated that culture time can be important for the final bone formation. Vehof et al 21 found in their study that cell-loaded titanium fiber mesh, without prolonged culturing, resulted in a very limited amount of bone after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Finally, the use of scaffold material and surface modifications, such as a calcium phosphate coating, can play an important role in stimulating the osteogenic potential of stromal cells. [18][19][20] In view of the aforementioned, our previous studies with titanium fiber mesh indicated that culture time can be important for the final bone formation. Vehof et al 21 found in their study that cell-loaded titanium fiber mesh, without prolonged culturing, resulted in a very limited amount of bone after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 45S5 ® Bioglass contains silica, a constituent that is lacking from the HA and TCP employed in this study. In previous studies characterizing the response of human osteoblasts seeded on silica surfaces without the interference of other ions present in glass ceramics, there were no apparent differences in cell number, metabolic activity, or ALP activity, yet nodule formation was accelerated on silica surfaces [40]. The importance of silica is confirmed in other studies demonstrating significant increases in ALP activity and type I collagen production by osteoblasts exposed to bioactive glasses with 46.1 mol% silica content (45S5) than cells exposed to bioactive glasses with 60 or 80 mol% silica (58S and 77S, respectively) [41].…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, both metabolic role (a co-factor for prolyl hydroxylase) and a structural role (stabilization of collagen) have been attributed to Si [52,65,67]. Recent advancement in scientific techniques have revealed the true physiological role of Si in bone and connective tissue formation by observing the high concentrations of non-dialyzable Si in connective tissues and their components, and that apical accumulation of Si at the growing front of bone increased bone mineralization [70], and matrix polysaccharides and proteins synthesis with Si supplementation [52,65]. Furthermore, Si in the form of orthosilicic acid has been shown to induce type I collagen secretion and gene expression by osteoblasts and osteoblast-like cells for bone cell maturation and bone formation [71,72].…”
Section: Role Of Silicon In Animalsmentioning
confidence: 99%